A Taxonomy of Coping Strategies and Discriminatory Stressors in Digital Gaming - Passmore, Cale J.; Mandryk, Regan L. (Frontiers in Computer Science, 2020)
Digital gaming’s many benefits starkly contradict its well-cited toxicity. To accurately understand and compare how players cope with discriminatory stress in the context of play, 241 U.S. players were surveyed on recurring sources of discrimination during gameplay and strategies for coping across ranging experiential prompts. Qualitative analysis created a taxonomy of discriminatory targets, discriminatory acts, and coping strategies specific to online digital play. We compare experiences, perceptions, and beliefs around coping across intersections of race, gender, and class (with notes on ability and age), and describe how player identities inform in-game behavior, exposure to types of discrimination, and how coping strategies are navigated. We discuss the accumulative, anticipatory, and intergenerational nature of discriminatory stress in gaming, its stratified effects on wellbeing, and the role of discrimination in belief formation as well as ability to advocate for oneself and others.